2011
DOI: 10.1074/jbc.m111.220921
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Insights into ASB2α, a Novel Regulator of Integrin-dependent Adhesion of Hematopoietic Cells

Abstract: By providing contacts between hematopoietic cells and the bone marrow microenvironment, integrins are implicated in cell adhesion and thereby in control of cell fate of normal and leukemia cells. The ASB2 gene, initially identified as a retinoic acid responsive gene and a target of the promyelocytic leukemia retinoic acid receptor ␣ oncoprotein in acute promyelocytic leukemia cells, encodes two isoforms, a hematopoietic-type (ASB2␣) and a muscle-type (ASB2␤) that are involved in hematopoietic and myogenic diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…Western blotting, immunofluorescence, and flow cytometry assays, we previously showed that ASB2␣ expression triggers polyubiquitination and proteasomal degradation of filamins (5)(6)(7)31). In keeping with our earlier studies (7), flow cytometric degradation assays show that the FLNa ABD is both necessary and sufficient for ASB2␣-mediated degradation as the isolated ABD is efficiently degraded following ASB2␣ expression, although FLNa lacking the ABD is resistant to degradation (Fig.…”
Section: Asb2␣ Targets Ch1 Of Flna For Degradation-usingsupporting
confidence: 62%
See 4 more Smart Citations
“…Western blotting, immunofluorescence, and flow cytometry assays, we previously showed that ASB2␣ expression triggers polyubiquitination and proteasomal degradation of filamins (5)(6)(7)31). In keeping with our earlier studies (7), flow cytometric degradation assays show that the FLNa ABD is both necessary and sufficient for ASB2␣-mediated degradation as the isolated ABD is efficiently degraded following ASB2␣ expression, although FLNa lacking the ABD is resistant to degradation (Fig.…”
Section: Asb2␣ Targets Ch1 Of Flna For Degradation-usingsupporting
confidence: 62%
“…We have established that ASB2␣ targets filamins for proteasomal degradation (5,6,31), have shown that the N-terminal region of ASB2␣ along with the first 10 ankyrin repeats supports ASB2␣ binding to filamins (31), and have revealed that the ABD of filamin mediates interaction with ASB2␣ and is sufficient for ASB2␣-mediated degradation (7). Here, we 155-165).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations